The localization of sites containing nascent RNA and splicing factors. - Pombo, A; Cook, P (1996)
Sites of transcription in the HeLa nucleus are not diffusely spread throughout euchromatin but are concentrated in approximately 2000 discrete sites or "transcription factories." These sites can be immunolabeled after allowing permeabilized cells to elongate nascent RNA chains in the presence of BrUTP. Splicing factors are also concentrated in a few tens of nuclear domains known as "speckles"; they are also more diffusely spread throughout euchromatin. As there has been some controversy whether the speckles are sites of transcription, we investigated the relative distributions of transcription factories and the speckles (detected using Sm autoimmune antibodies). We used conditions that minimize the redistribution of both the nascent RNA and the antigens during permeabilization and fixation and imaged the sites with high resolution using cryosections and a "confocal" microscope. The speckles contained little-if any-nascent RNA and so were usually not transcriptionally active, but they were often surrounded by a few transcription sites. Whether they are active sites of processing of RNA or merely sites where the machinery is stored remains to be established.